Positive inotropic effects of serotonin in atrial EHT: further proof for an atrial phenotype? - Muhammed Sönmez; Margaret Nandudu; Paul Brunnbauer; Carl Schulz; Birgit Klampe; Thomas Schulze; Arne Hansen; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) cultured in the presence of retinoic acid were proposed as a model for human atrium. Since in the human heart positive inotropic effects of serotonin (5-HT) are restricted to the atrium, we investigated whether the presence of 5-HT responses may distinguish between hiPSC-atrial and ventricular CM. Nonfiltered retinoic acid (1 µM) was used to induce an atrial phenotype (hiPSC-aCM) in two different hiPSC lines. Untreated hiPSC-CM were used as controls (ventricular). We measured 5-HT4 receptor ( HTR4 ) expression and 5-HT effects on Ca 2+ currents (I Ca ), force, and action potential in engineered heart tissue (EHT). HTR4 transcript abundance was five times higher in atrial EHT. 5-HT (100 µM) increased I Ca from 5.3 ± 0.8 to 8.1 ± 1.1 pA/pF, prolonged APD 20 from 8.1 ± 1.2 to 12.0 ± 1.2 ms, and shortened APD 90 from 142.3 ± 11.3 to 117.0 ± 6.6 ms in hiPSC-aCM, but not in hiPSC-vCM. 5-HT increased force in atrial EHTs from 0.06 ± 0.01 to 0.10 ± 0.01 mN but not in vEHT. Spontaneous beating rate per minute was increased by 5-HT in aEHT from 151.3 ± 7.5 to 173.7 ± 4.1 and in vEHT from 43.1 ± 4.2 to. 61.3 ± 3.4. Both EHTs contain functional 5-HT receptors, but 5-HT increases I Ca and force only in aEHT, similar to the human heart. In vEHT, 5-HT’s positive chronotropic effect in the absence of I Ca stimulation and inotropic response suggests activation of funny channels. Our findings demonstrate that aEHT shares the typical atrial-selective regulation of I Ca and force by 5-HT, thus making aEHT a promising model to study 5-HT 4 receptors in the human heart.